Saberes não sabidos ou saberes não reconhecidos?: professores especialistas e suas memórias no trabalho com estudantes com deficiência - Sant’Anna, Iara Gonçalves de Aguiar (2023)
This masters research aimed to collaborate with teacher training processesto work with students with disabilities in Middle School, and it is justified by the necessity to find new training possibilities since the reports produced by the professionals of the researched school show that academic teacher training is insufficient for the school’s inclusion demands. Teachers’ memories about building pedagogical knowledge on the inclusion of people with disabilities was admitted as the object of this research. General objective was to identify experiences by Middle School teachers that contributed to building pedagogical knowledge on how to work with students with disabilities. Specific objectives were: a) to raise awareness to teacher experiences on working with people with disabilities; b) to identify emotions and feelings involved in such experiences; and c) to identify inductive situations for such emotions and feelings. Methodology used for producing information was a questionnaire for participants’ characterization, the writing of a critical incident, and semi-structured interviews. Prose analysis, by André (1983), inspired the analysis and discussion of the information produced. Theoretical framework took Henri Wallon’s (1986) psychogenetic theory, complemented by Mahoney & Almeida (2005), Gatti (2014), Bosi (1994), Damásio (2022), Ezpeleta & Rockwell (1989), Prandini (2010), Lima (2018) and Lüdke & André (1986). Results showed that affectivity and recalling memories are responsible for building teaching knowledge, or practical knowledge, which have an extremely important role in teachers’ training process, beyond the knowledge of their subjects